PENGEMBANGAN UMKM MAKANAN WONTON DI KOTA BARU DRIYOREJO - Permadi, Edo Galih; Waras, Waras; Muzakki, Muzakki; Aristyanto, Erwan (DedikasiMU : Journal of Community Service, 2025)
The partner in this community service program is Wonton UMKM entrepreneur. The problems faced by the partner are inadequate production equipments, lack of product variety, lack of marketing tools and strategies, and lack of systematic financial records. To overcome these problems, researchers used several methods, such as providing food grinding tool (chopper), freezer, and banner that show products and brand logo, providing training in the use of social media and e-commerce as marketing media, designing business brand logo, training in making systematic financial record using Microsoft Excel, and providing training and assistance to partner in running a business based on management theories. As the results, the partner can increase their production capacity, increase sales, and make systematic financial records.